2022
DOI: 10.3390/genes13101760
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell RNA-Seq Identifies Immune-Related Prognostic Model and Key Signature-SPP1 in Pancreatic Ductal Adenocarcinoma

Abstract: There are no reliable biomarkers for early diagnosis or prognosis evaluation in pancreatic ductal adenocarcinoma (PDAC). Multiple scRNA-seq datasets for PDAC were retrieved from online databases and combined with scRNA-seq results from our previous study. The malignant ductal cells were identified through calculating copy number variation (CNV) scores. The robust markers of malignant ductal cells in PDAC were found. Five immune-related signatures, including SPP1, LINC00683, SNHG10, LINC00237, and CASC19, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…This is consistent with the characteristics of immune cells infiltrated into the cancer tissue. Given the significant differences among malignant ductal cell subpopulations from different PADC patients, 34 , 35 we acknowledge the limitation of the characterization on the three tumor populations from a single patient. In future study, scRNA-seq from large cohort with sufficient normal pancreas ductal cells are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the characteristics of immune cells infiltrated into the cancer tissue. Given the significant differences among malignant ductal cell subpopulations from different PADC patients, 34 , 35 we acknowledge the limitation of the characterization on the three tumor populations from a single patient. In future study, scRNA-seq from large cohort with sufficient normal pancreas ductal cells are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SPP1 expression in LUAD tissues was signi cantly higher than in normal tissues, positively correlated with TNM stage, lymph node metastasis, and depth of in ltration, and was associated with poorer prognosis by upregulating COL11A1 expression to promote cell migration and invasion (Yi et al, 2022). And in pancreatic adenocarcinoma, SPP1 expression levels were associated with patient prognosis and immune regulation (Chen et al, 2022), and in lung adenocarcinoma, SPP1 was found to be associated with drug resistance (Matsubara et al, 2022). In a recent study, researchers further investigated the level of serum SPP1 autoantibodies in patients with esophageal squamous cell carcinoma (ESCC) and showed that its expression was signi cantly upregulated compared to the normal group, suggesting that anti-SPP1 autoantibodies are a novel biomarker for the detection of ESCC , and SPP1 is important in prostate cancer (PCa), head and neck cancer (HNC), cervical squamous cell carcinoma (SCC) and other cancers (Zhang et al, 2022, Feng et al, 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 46 • SPP1 is an immune marker which is abundant in type 2 ductal cells and M2 macrophage in PDAC.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Furthermore, Chen et al 46 performed scRNA‐seq and revealed M2 macrophage showed a higher expression of immune marker, SPP1, in PDAC compared to those in normal pancreatic tissues. Using multicolor immunohistochemistry (IHC) staining further analysis revealed abundant chemokines and ligands in M2 macrophage, which induced tumor development in PDAC 46 . This suggested SPP1 is a potential prognostic biomarker in PDAC, considering its abundance in type 2 ductal cells and M2 macrophage, both of which were involved in tumor‐related characteristics.…”
Section: Single‐cell Analysis In Primary Pdac Tumors and Metastatic L...mentioning
confidence: 99%